Proposing empirical research : a guide to the fundamentals - Patten, Mildred L.
Proposing Empirical Research: A Guide to the Fundamentals provides step-by-step instructions for students who will be writing their first research proposal in the social and behavioral sciences and using both quantitative and qualitative methods. The structure of the book enables students to work independently with confidence while writing the first drafts of their proposals. Each major section is divided into short topics and for each topic, students are asked to complete an exercise that leads them toward the goal of preparing a proposal. Numerous illustrative examples throughout the book make the recommendations for proposal writing come alive. In addition, the 10 model proposals provided at the end of the book illustrate proposal writing and provide material for classroom discussions. New to the Sixth Edition: 1.- Updates throughout to reflect research and learning in the digital/online environment, e.g., online surveys, digital organization tools, digital recruitment methods for research, and digital databases, records, and archives. 2.- Discussion of qualitative methods. 3.- Updated references, model proposals, end of chapter exercises etc. Proposing Empirical Research is ideal for use in research methods classes where students write a proposal as a term project, thesis/dissertation preparation classes, senior research seminars where proposing and conducting research is a culminating undergraduate activity, and any graduate-level seminar in which the instructor wants to incorporate a project that will engage students in critical thinking about the content area.